IMPLEMENTASI STRATEGI PEMBELAJARAN TEMATIK PADA MATA PELAJARAN PAI - Nurul Qalbi (STAI Kuala Kapuas, 2026)
Thematic learning strategy is the main approach in the 2013 Curriculum which aims to integrate various subjects in one theme, including Islamic Religious Education (PAI) and Character Education. This approach is expected to be able to shape the character and spirituality of the students who are educated through contextual, active, and meaningful learning. This study aims to analyze the implementation of thematic learning strategies in PAI and Character Education subjects and identify the advantages and challenges faced. The method used is qualitative research with a literature review approach. Data were collected from various scientific articles and explained using content analysis techniques. The results of the study show that thematic learning strategies have characteristics that are centered on students, provide direct experience, and flexibly unite various subjects in one theme. This strategy increases learning motivation and encourages collaboration and critical thinking skills. However, its implementation still faces challenges such as lack of teacher understanding of the thematic curriculum, limited contextual open materials, and difficulties in evaluation. This strategy is implemented through three main stages: planning, implementation, and evaluation. In conclusion, thematic learning strategies have great potential in increasing the effectiveness of PAI and Character Education learning. The success of implementing this strategy is highly dependent on the readiness of educators and the support of educational institutions in overcoming existing challenges.